Website Quality Measurement of Higher Education Services Institution Region IV Using Webqual 4.0 Method - Rintho Rante Rerung; Muhammad Fauzan; Hari Hermawan (Indonesian Scientific Journal, 2020)
The purpose of this study is to measure and describe the Higher Education Services Institution Region IV website quality using the Webqual 4.0 method. The questionnaire filling, depth interviews, and observation are the methods used in this research. The measurement results showed that the overall of the Higher Education Services Institution Region IV website quality was included in Good criteria. In detail from the measurement results, the dimension criteria that gained the highest score was the usability dimension which is 741,63 with a percentage of 81.05 (good criteria). The information quality dimension obtained an average score of 730,57 with a percentage 79.84 (good criteria). While the dimension that obtained the lowest score was the service interaction dimension which was 710,50 with the percentage of 77.10 (good criteria). In addition, in order to accommodate the needs of visitors, this study found the fact that visitors expected website developers to build the website navigate easily, information updated more, implement a comprehensive recommendation system, and more interactive.